Pharmaceutical Development of «Sedoflav» Capsules, Standardization and Validation of Flavonoids Assay Methods - M. A. Dzhavakhyan; M. G. Tokareva; Yu. E. Prozhogina; E. I. Kalenikova (Разработка и регистрация лекарственных средств)
Introduction. Creating a new herbal remedy with a mild generalized effect is an urgent task of modern pharmacology and pharmaceutical technology. The dosage form of an innovative medicinal product should take into account its properties, ensure the effectiveness of the drug and ease of intake.Aim. Creation of hard gelatin capsules with a plant composition-dry extract and validation of methods for quantifying the amount of flavonoids for the preparation of draft regulatory documentation.Materials and methods. The physicochemical and technological properties of the developed dry extract, as well as experimental capsule masses, such as mass loss during drying, bulk volume and granulometric composition, flowability, angle of natural slope, compaction, and parameters of the obtained capsules (solubility, disintegration, etc.) were studied according to the methods described in the State Pharmacopoeia of the XIV edition. Methods were developed for quantitative determination of flavonoid content in terms of rutin in dry extract and capsules using differential spectrophotometry, which were validated.Results and discussion. During the study of the experimental dry extract, its high hygroscopicity was found, which worsens its technological properties and complicates the encapsulation process. As a result of the addition of auxiliary substances, such as anhydrous lactose and talc, it was possible to obtain an optimal mass for encapsulation, which served as the basis for the creation of the drug «Sedoflav».Conclusion. On the basis of a dry extract of plant composition capsules «Sedoflavt» were developed, its standardization was produced. Methods for quantifying the amount of flavonoids in terms of rutin in experimental dry extract and capsules have been developed and validated.